محاضرات في التقويم التربوي - بونيف حنان (جامعة محمد بوضياف -المسيلة, 2026)
يعد التقويم جزءا متكاملا من العملية التعليمية التعلمية يؤثرفي كل جوانبها ويتأثربها ويزيدمن فاعليتها ويجعلها في المسار الصحيح،كما أن فوائد التقويم ليست حكراعلى فئة واحدة بل ممتدة إلى فئات عديدة سواء المعلمون أو المتعلمون أو أولياء الأمور وكذا صانعوا السياسات التعليمية.نحاول في هذه المطبوعة البيداغوجية معالجة جميع الموضوعات المقررة في البرنامج الوزاري والمنتقاة بما يحقق الفائدة لطالب علم اجتماع التربية بداية من: التقويم التربوي: المفهوم والنشأة والأهمية، التقويم والأهداف التربوية ثم الوظائف الاجتماعية للتقويم كما تم التطرق إلى أدوات التقويم التربوي بالتفصيل وتم تناول عناصر الفعل التقويمي : المعلم،المتعلم،الموضوع،شروط الانجاز،التصحيح يضاف إلى ذلك علم التباري و التقويم التربوي وجملة من النماذج حول الدراسات الدوسيمولوجية وآخر محاضرة حول تقييم وتقويم الكفاءات من خلال تحليل التقويم التربوي في المدرسة الجزائرية مع الإشارة إلى امتحان تقييم المكتسبات الذي يمثل نقلة نوعية من الكم إلى الكيف في عملية التقويم. الكلمات المفتاحية: التقويم التربوي، الأهداف التربوية، شروط الإنجاز، الاختبارات التحصيلية، علم التباري، المقاربة بالكفاءات. Assessment is considered as an integral part of the teaching and learningprocess, influencing and being influenced by all its aspects, enhancingitseffectiveness, and keepingit on the right track. Furthermore, the benefits of assessment are not limited to one group but extend to many, includingteachers, learners, parents, and educationalpolicymakers. In thispedagogical publication, weattempt to address all the topicsincluded in the ministerial curriculum, selected to benefitstudents of the sociology of education.Startingwith: Educational Assessment: Concept, Origin and Importance, Assessment and Educational Objectives, then the social functions of assessment. The tools of educationalassessmentwerealsodiscussed in detail, and the elements of the assessmentprocesswereaddressed: the teacher, the learner, the subject, conditions of achievement, correction. In addition, Docimologyand educationalassessment and a number of models on docimological studieswerediscussed, and the last lecture was on the evaluation and assessment of competenciesthrough an analysis of educationalassessment in the Algerian school, Highlightingthe achievementassessment exam, whichrepresents a qualitative shift fromquantity to quality in the assessmentprocess. Keywords: Educational assessment, educational objectives, achievementrequirements, achievement tests, Docimology, competency-basedapproach.
السنة الأولي ماستر علم الاجتماع التربوي